Evaluating FSKM website quality using academic website quality evaluation framework / Darrold Hansen Mathew - Mathew, Darrold Hansen (2014)
Web sites has been evolved since the beginning of Internet to serves information users electronically. Similar to products, web site has to be categorized into elements that can be measured so that the evaluation can come up with the level of quality which the web site possessed. Objectives of this study were to evaluate the quality of FSKM website using Academic Website Quality Evaluation Framework and to provide recommendations for FSKM website quality improvement. The proposed framework which is Academic Website Quality Evaluation Framework is designed specifically for academic website quality evaluation. The sample of this study were the students of Bachelor of Information Technology (CS240) and Master of Science in Information Technology (CS770), Faculty of Computer and Mathematical Sciences, Universiti Teknologi Mara Shah Alam. There were five (5) phases conducted in order to complete this study methodology; instrument preparation (phase one), online survey (phase two), interview (phase three), data analysis (phase four), and findings and conclusion (phase five). Online survey were used to gather quantitative data during Phase 2 of the study, while open-ended questions used for the interview sessions in Phase 3 to gather qualitative data.